Flipping the EFL classroom in a secondary education setting: Students’ perceptions and academic performance - Bueno Alastuey, Mª Camino; Andres Galar, Itxaso (Huarte de San Juan. Filología y Didáctica de la Lengua, 2017)
The flipped classroom teaching model has gained a lot of popularity lately. The core idea of this new approach is to switch the class sequence moving direct instruction out of the classroom by making students watch videos that explain the content before coming to class. This way in-class time is freed up to implement student-centred activities that engage students and enhance active learning. Despite its popularity, studies regarding the implementation of the flipped classroom focus mainly on fields that are strongly based on lecturing, such as science, technology and mathematics, and on university settings. This case study aims to contribute to research on the implementation of the flipped classroom by extending it to an EFL classroom in a Secondary Education setting. Results obtained in pre and post-tests and in questionnaires showed that the flipped classroom improved students’ academic performance and this new teaching model was perceived positively by students.